The theory of total possibility and the hypothesis of the intellect: Towards a new foundation for metaphysics - Hernández Quiroz, Anselmo (2025)
I return to the problem of the proper field of metaphysics and its justification as an intellectual science. I define it with respect to the fundamental object that in my opinion it presupposes: the total possibility (the set of the manifested and the unmanifested). To support it, I propose, through n Aristotelian rereading, the hypothesis of the intellect.